Discovery of a Novel, Paternally Expressed Ubiquitin-specific Processing Protease Gene through Comparative Analysis of an Imprinted Region of Mouse Chromosome 7 and Human Chromosome 19q13.4 - Kim, Joomyeong; Noskov, Vladimir N.; Lu, Xiaochen; Bergmann, Anne; Ren, Xiaojia; Warth, Tiffany; Richardson, Paul; Kouprina, Natalya; Stubbs, Lisa

(untitled) (Genome Research, 2000)
Using mouse BAC clones spanning an imprinted interval of proximal mouse chromosome 7 and the genomic sequence of the related interval of human chromosome 19q13.4, we have identified a novel mouse gene,Usp29 (ubiquitin-specific processing protease 29), near two known imprinted genes, Peg3 and Zim1. GeneUsp29 is located directly adjacent to Peg3 in a “head-to-head” orientation, and comprises exons distributed over a genomic distance of at least 400 kb. A similar human gene is also found in the homologous location in human chromosome 19q13.4. The mouseUsp29 gene is also imprinted and is transcribed mainly from the paternal allele with highest expression levels in adult brain, especially in the cerebral cortex and hippocampus, and in the forebrain, face, and limb buds of midgestation mouse embryos. Analysis of a full-length 7.6-kb cDNA clone revealed that Usp29 encodes an 869-amino-acid protein that displays significant homology with yeast and nematode ubiquitin carboxyl-terminal hydrolases. These data suggest that, like the candidate Angelman syndrome gene Ube3a(ubiquitin ligase), Usp29 may represent another imprinted gene involved in the ubiquitination pathway. This identification of a third imprinted gene, Usp29, from the Peg3/Zim1-region confirms the presence of a conserved imprinted domain spanning at least 500 kb in the proximal portion of mouse chromosome 7 (Mmu7).[The sequence data described in this paper have been submitted to the GenBank data library under accession nos. AF229257 andAF229438.]